HRM in development: lessons and frontiers - Berman, Evan M. (2015)
This article discusses contributions of human resources management (HRM) to strengthening state institutions in development settings. It also identifies leading practices and frontiers in HRM practice and research.Technical HRM expertise in development exists in matching organizational performance with staffing, advancing decentralization, international project management, and training, and research also shows extensive concerns with patronage and anti-corruption. Frontiers are discussed in connection with strategic HRM, notably improved leadership development/talent management, workforce engagement in developing settings, re-thinking/professionalization of appointee executive relations, comprehensive HRM strategies, and increased leadership for HRM itself. Although development studies often raise HRM implications, relatively few focus on HRM in development in a comprehensive fashion. - Reproduced.
Keywords: Human resources development